2011
DOI: 10.1308/003588410x12771863936846
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in the management of Hirschsprung’s disease in the UK and Ireland: a national survey of practice revisited

Abstract: INTRODUCTION The management of Hirschsprung’s disease continues to evolve. This questionnaire survey aimed to determine current surgical management strategies for Hirschsprung’s disease in Britain. SUBJECTS AND METHODS The survey was sent electronically to all British paediatric surgeons. Initial questions explored individual experience and regional service provision. Additional questions, reserved for surgeons who perform definitive Hirschsprung’s disease surgery, addressed specific clinical scenarios. RESULT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 18 publications
7
47
0
Order By: Relevance
“…This indicates that with a low case load per surgeon the training opportunities for new surgeons may be limited. A similar conclusion was drawn for the treatment of Hirschsprung disease in the survey conducted in the UK by Bradnock et al [3].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This indicates that with a low case load per surgeon the training opportunities for new surgeons may be limited. A similar conclusion was drawn for the treatment of Hirschsprung disease in the survey conducted in the UK by Bradnock et al [3].…”
Section: Discussionsupporting
confidence: 79%
“…Several surveys on the management of other colorectal diseases, such as Hirschsprung disease (HD), have been published [3,4]. A survey among pediatric surgeons from the UK showed that the primary pull-through during the first 3 months of life, using an open Duhamel or laparoscopic-assisted Soave-Boley technique, had become the operative strategy of choice in rectosigmoid HD in the UK.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Similar survey of members of British Association of paediatric surgeons (BAPS) in 2008 showed equal preference for both Soave and Duhamel procedures. [14] Since the introduction of complete transanal pull through for HD by De la Torre-Mondragón and Ortega-Salgado in 1998, [4] many groups have reported on this procedure and have shown it to be a safer option. [15][16][17][18][19] It is a simple approach eliminating the need for abdominal access by either laparoscopy or laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…[30] A recent survey of BAPS members by Bradnock and Walker revealed that 86% of 36 respondents now performed primary pull through in a well-child. [14] Singh et al in a survey of 126 children managed for HD on a prospective basis over 4 years by members of the AAPS reported that 51% of the children had primary pull through. [5] The findings of the of the present survey with only 40% of the respondents performing primary pull through for more than half of their patients is rather low compared with other reports.…”
Section: Discussionmentioning
confidence: 99%